SISTEM INFORMASI PELAYANAN KESEHATAN MASYARAKAT BERBASIS WEB (Information Technology and Telematics, 2014)
Semarang west region is a vast territory, with sixteen wards. There are many relic in health clinics or doctors ' practices. Existing problems, namely the presence of electronic media has not been able to locate and display the data doctor's practice schedule and in particular the region West of Semarang. The purpose of this research is to generate service information system website doctor (a case study in the city of Semarang health service) which is able to present a doctor's practice schedule information. The programming language used is PHP and using a MySQL database. Analysis tools are used namely easycase and macromedia dreamweaver. The results of this research are generating website services other than physician practice, facilitate information searches, as well as improving the effectiveness and efficiency of the performance of doctors. The conclusion of this Activity the doctor search is one of the five health efforts in the Ministry of public health in General. Keywords: Website, PHP and MySQL